Giving Rewards as an Attempt to Increase Teacher Motivation at SDN 006 Kota Baru Kampar - Ahmad Sukardi (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
This paper investigates a study that aims to find out whether motivational achievement can be increased through giving rewards at SDN 006 Kota Baru Kampar or not. If the teachers have motivational achievement, they will carry out their work seriously to achieve the success of the organizational goals that have been determined. In addition, the focus of the research is related to reward giving as an attempt to increase teachers’ motivational achievement. The research is school action research (PTS), which was carried out at SDN 006 Kota Baru Kampar. The research subjects involved 19 teachers. The research was conducted in two cycles. Based on the description of data processing and discussion, it is concluded that motivational achievement can be increased through giving rewards at SDN 006 Kota Baru Kampar. It can be seen from the aspect of giving rewards presented by the teachers, which indicates that it increased from cycle I to cycle II. If the average score indicates 20 in cycle I, then it increases to the average score of 32 in cycle II. In terms of teacher motivational achievement, it is found that in cycle I the average percentage is 52.6% with a fairly good category and in cycle II it increases to 86.8% with very good category.